Branding for province: is it useful? Study on branding communications of Jateng Gayeng in the Ganjar Pranowo’s leadership - Andre Noevi Rahmanto (Informasi, 2022)
The Central Java Provincial Government launched the slogan and logo for the Jateng Gayeng but in practice it is not easy because of the different roles of the provincial government in the era of regional autonomy. While on the other hand, many regency/municipal already have their own branding. This research with a qualitative approach was conducted to examine the branding process of the Central Java Provincial government through the branding of Jateng Gayeng. A series of qualitative interviews with four key informants, focus group discussions attended by twelve regency/municipal government representatives, and document analysis were conducted to examine the processes involved in designing and implementing branding. The results showed that in branding Jateng Gayeng, the government of Central Java Province was more likely to use secondary communication in the form of logos and slogans. Communication with stakeholders is more likely to use an informative strategy than a collaborative one. The emergence of provincial branding in Central Java has useful and potential to strengthen district/city branding.